Sleep duration over 28 years, cognition, gray matter volume, and white matter microstructure: a prospective cohort study - Zitser, J; Anatürk, M; Zsoldos, E; Mahmood, A; Filippini, N; Suri, S; Leng, Y; Yaffe, K; Singh-Manoux, A; Kivimaki, M; Ebmeier, K; Sexton, C (Oxford University Press, 2020)
Study Objectives: To examine the association between sleep duration trajectories over 28 years and measures of cognition, gray matter volume, and white matter microstructure. We hypothesize that consistently meeting sleep guidelines that recommend at least 7 hours of sleep per night will be associated with better cognition, greater gray matter volumes, higher fractional anisotropy, and lower radial diffusivity values.